Gender differences in wheelchair marathon performance - Oita International Wheelchair Marathon from 1983 to 2011 - Lepers, R.; Stapley, P. J.; Knechtle, B. (Open Access Journal of Sports Medicine, 2012)
Background: The purpose of the study was (1) to examine the changes in participation and performance of males and females at the Oita International Wheelchair Marathon in Oita, Japan, between 1983 and 2011, and (2) to analyze the gender difference in the age of peak wheelchair marathon performance. Methods: Age and time performance data for all wheelchair athletes completing the Oita International Wheelchair Marathon from 1983 to 2011 were analyzed. Results: Mean annual number of finishers was 123 ± 43 for males and 6 ± 3 for females (5.0% ± 2.0% of all finishers), respectively. Mean age of overall finishers was significantly (P = 0.026) greater for males (41.3 ± 1.8 years) compared to females (32.7 ± 1.4 years). In contrast, there was no difference in the mean age of the top three overall finishers between males (35.8 ± 3.2 years) and females (31.6 ± 1.5 years). The race time of the top three overall finishers was significantly lower (P < 0.01) for males (1:34 ± 0:11 hours:minutes) compared to females (1:59 ± 0:20 hours:minutes), but it was not significantly different between male (2:06 ± 0:12 hours:minutes) and female (2:12 ± 0:18 hours:minutes) overall finishers. The mean gender difference in time was 26.1% ± 9.7% for the top three overall finishers. Conclusion: Further studies are required to investigate the reasons for the low participation of females in wheelchair marathons and why the gender difference in marathon performance is much greater for disabled athletes than for able-bodied athletes.